2021
DOI: 10.7566/jpsj.90.014702
|View full text |Cite
|
Sign up to set email alerts
|

Formations of Narrow Stripes and Vortex–Antivortex Pairs in a Quasi-Two-Dimensional Ferromagnet K2CuF4

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/224185/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…For KCuF, this window is at low temperatures (the exact window is discussed in detail later), where a modified Kosterlitz–Thouless (KT) transition was observed through neutron scattering and static magnetization measurements reported almost 40 years ago (Hirakawa, 1982). In our recent work on this material (Togawa et al, 2021), we reported real-space, direct observations of vortex and antivortex structures at a single temperature, consistent with the excitation types expected from the KT transition (Berezinskii, 1971, 1972; Kosterlitz & Thouless, 1973), but possibly modified by anisotropies arising from the finite sample size.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…For KCuF, this window is at low temperatures (the exact window is discussed in detail later), where a modified Kosterlitz–Thouless (KT) transition was observed through neutron scattering and static magnetization measurements reported almost 40 years ago (Hirakawa, 1982). In our recent work on this material (Togawa et al, 2021), we reported real-space, direct observations of vortex and antivortex structures at a single temperature, consistent with the excitation types expected from the KT transition (Berezinskii, 1971, 1972; Kosterlitz & Thouless, 1973), but possibly modified by anisotropies arising from the finite sample size.…”
Section: Introductionsupporting
confidence: 78%
“…We note that the nonrigid analysis methodology developed in Part I of this work and used here allowed the inclusion of the entire sample and support structure areas in these analyses. This was not possible in our earlier work (Togawa et al, 2021) on account of the choice of the B-spline basis (Arganda-Carreras et al, 2006; Schindelin et al, 2012) for the distortion field.…”
Section: Ctem and Fresnel Imagesmentioning
confidence: 85%
See 1 more Smart Citation
“…In Part II of this work (Paterson et al, 2021), we apply the TEM-DPC technique to experimental cryo-TEM Fresnel images of the magnetic phase transition of a thin lamella of KCuF, a material of interest for its quasi 2D ferromagnetism at low temperatures (Hirakawa, 1982; Togawa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, using cryogenic Lorentz transmission electron microscopy, we investigate the temperature evolution of magnetic structures in single crystal samples of K2CuF4 with a magnetic phase transition at 6.1 K [2]. This material is one of the candidates for a 2D XY magnet that may exhibit the BKT phase transition.…”
mentioning
confidence: 99%